Experiences of the Hungarian EU funding in the 2014-2020 budgetary period - Gábor Ferenc Kiss; Tamás Stukovszky (Köz-gazdaság, 2021)
The aim of the paper is to analyse the implementation of Hungarian EU funding in the most recent budgetary period which ended in 2020. The research examines the intervention fields aimed by the operational programmes and the statistics of grant applications as well. In addition, the study gives a detailed analysis about the economic development programme compared to the one in the previous financial cycle. Overall, the aim is to seek the funding practice in Hungary regarding to the sectoral priorities and the characteristic of regional allocation.